A supramolecular hydrogel prepared from a thymine-containing artificial nucleolipid: study of assembly and lyotropic mesophases. Issue 34 (16th August 2018) - Zhang, Dawei; Liu, Qingkun; Visvanathan, Rayshan; Tuchband, Michael R.; Sheetah, Ghadah H.; Fairbanks, Benjamin D.; Clark, Noel A.; Smalyukh, Ivan I.; Bowman, Christopher N.
Abstract : Study of assembly and lyotropic mesophases in a supramolecular hydrogel composed of a thymine-containing artificial nucleolipid (TTPC). Abstract : An artificial nucleolipid containing thymine, a triazole-ring, and phosphatidylcholine (TTPC) moieties was prepared by copper catalyzed azide alkyne cycloaddition (CuAAC) under aqueous conditions. The resulting TTPC molecules assembled in situ into a fibrous aggregation. The study of the TTPC fiber assembly using XRD and NMR spectroscopy revealed that the formation of fibers was driven by the unique combination of the lipid and nucleobase moieties in the structure of TTPC. At a critical TTPC concentration, entanglement of the fibers resulted in the formation of a supramolecular hydrogel. Investigation of the lyotropic mesophases in the TTPC supramolecular hydrogel showed the presence of multiple phases including two liquid crystal phases ( i.e., nematic and lamellar), which have a certain degree of structural order and are promising templates for constructing functional biomaterials.